Juridical Analysis of Khamar Crimes in the Perspective of Aceh Qanun Number 6 of 2014 Concerning Jinayah - Mustakim Mustakim; Muhammad Riza (LAW & PASS: International Journal of Law, Public Administration and Social Studies, 2024)
Historical developments in the prohibition of alcohol in Aceh refer to Islamic Sharia which firmly and clearly prohibits and forbids alcohol for all Muslims. Because one of the maqashids of Sharia is to maintain reason, Islamic Sharia strictly prohibits this. The prohibition on alcohol is sharia in the Al-Qur'an and Hadith. The punishment in Aceh is to implement Islamic Sharia as a whole (kaffah), by applying Islamic Sharia in various aspects of life, including in this case applying the punishment of caning to perpetrators of the crime of drinking wine. Caning is used as a crime with the aim of fostering and educating perpetrators to be aware and regret their actions and also as a lesson (tadabbur) to society so that they do not commit the same actions.